Efektivitas Cyber Patrol dalam Mengungkap Kasus Pornografi di Polresta Denpasar - Putu Diah Wiska Sasmitha; I Nyoman Gede Sugiartha; I Nyoman Subamia (Jurnal Analogi Hukum, 2022)
Indonesia with a large population has a lot of potential for social change from various backgrounds and ages. Social media has a positive impact and has a negative impact illegal content through social media in the form of pornography, copyright infringement, virtual terrorism, and gambling using cyber media. Pornography is one of the most common offenses on social media by presenting videos, photos and stories. The existence of this case made the POLRI anticipate pornographic crimes and form a team called cyber patrol to eradicate crime in cyberspace. The formulation of the problems in this research, including: 1) How cyber patrol carried out by Denpasar Police investigators in uncovering pornography cases? and 2) What are the factors that hinder Denpasar Police investigators from carrying out cyber patrol to uncover pornography cases? In this study using the empirical method, with a sociological approach. The results of this study are the effectiveness of cyber patrol conducted by Denpasar Police investigators in uncovering pornography cases, namely by legal factors, law enforcement factors, facilities or facilities, community factors, cultural factors and factors that hinder Denpasar Police investigators in conducting cyber patrol to reveal pornography cases, namely internal factors and external factors.